TRECB (Transformative Reflexive Empowering Character Building) Based Practice Student Profile in Elementary Schools - M. Bambang Edi Siswanto; Suryanti Suryanti; Mochammad Nursalim; Siska Nur Wahida (Edumaspul: Jurnal Pendidikan, 2024)
The era is so sophisticated, information is developing rapidly, of course accompanied by side effects, namely moral decline, thus the researchers take a solution attitude. The purpose of this study is to determine the effectiveness of the application of the TRECB model. Information Gathering, Planning, developing initial product forms, initial field tests, main product revisions, main field tests, operational product revisions, operational field tests, final product revisions, and dissemination and implementation of the results of the research from 7 schools the researchers visited 60% that is 4 schools have implemented character education, then 3 schools still have not used the right method in its implementation so researchers found an effective formula in formulating the TRECB model character education with 4P+1i services namely introduction, practice, repetition, habituation , and internalization, research results this is the realization of a significant change of 80% to the realization of an internalized character profile in students, character habituation has begun to cultivate the essence of children who are consciously carrying out good behavior, so that it can be concluded that the idea of developing the TRECBEducational Model is a solution to reflect better changes in student character elementary school that we desire without any coercion the students carry out good character habituation.